Making peace with faith: the challenges of religion and peacebuilding - Garred, Michelle; Abu-Nimer, Mohammed (Peace and security in the 21st century series, 2018)
In this text, practitioners from different faiths relate and explore the many challenges they face in their peacebuilding work, which their secular partners may be unaware of. The contributors are all practitioners whose faith or religious experience motivates their work for peace and justice in such a way that it influences their actions